Filling the mitochondrial copper pool - Winge, Dennis R. (J Biol Chem, 2018)
A host of critical metalloproteins reside in mitochondria, where metallation occurs within the organelle after protein import. Although the pathways by which proteins are imported into the mitochondria are well known, the mechanisms by which their metal partners are imported are more obscure. A new study by Boulet et al. demonstrates that the mammalian SLC25A3 inner membrane transporter, previously known as a phosphate carrier, is also a functional Cu(I) importer, clarifying the source of mitochondrial copper and raising new questions about cellular copper homeostasis.